Hubungan Penerimaan Diri dengan Kemandirian Psikososial Anak Berkebutuhan Khusus - Wahyudi, Syifa' Salsabila; Barida, Muya (Buletin Konseling Inovatif, 2025)
Students with a physical disability with high self-understanding will form an attitude of acceptance of themselves, but it will also foster an attitude of psychosocial independence. The existence of self-acceptance from students with disabilities will promote good psychosocial independence, so it is necessary to strengthen the student with disabilities to accept their current conditions. This study aimed to determine whether or not there is a correlation between self-acceptance and psychosocial independence of students with disabilities in special schools in Yogyakarta. This research used a correlational design. The subjects of this study were students with disabilities who attended several special schools in Yogyakarta, with a total sample of 30 students with disabilities. The research instrument is a psychological scale of self-acceptance and psychosocial independence. The data analysis method used a non-parametric statistical analysis technique, the Spearman Rank Test. This method is used because one data is not normally distributed. The results of this study can be concluded that there is a correlation between self-acceptance and psychosocial independence of special school students with disabilities in Yogyakarta.